FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI PADA PASANGAN USIA SUBUR (PUS) DI DESA PENFUI TIMUR WILAYAH KERJA PUSKESMAS TARUS KABUPATEN KUPANG - Maria Trifonia Mole Huar noning; Maria Paula Marla Nahak; Yohanes Dion (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
The low rate of contraceptive use illustrates the failure to implement family planning programs in a region. Coverage of CPR (Contraception Prevalence Rate) in East Penfui Village is 14.2%. The figure is still far from the national target of 66%. The factor that can influence the use of contraception is knowledge, information on health workers and community socio-culture. The purpose of this study was to determine the corelation between knowledge, information on health workers, socio-culture with contraceptive use in the East Penfui village, the working area of Puskesmas Tarus, Central Kupang District, Kupang Regency. This research is a descriptive analytic study with cross sectional method. The sample size was 113 couples of fertile age who were determined by means of multistage random sampling from 5 hamlets in the village of East Penfui, The instrument used was a questionnaire, the results were analyzed using the chi-square test with a 95% confidence level. The results showed, respondents who used contraception 46.9%, respondents with good knowledge were 98.2%, respondents who were exposed to information from health workers were 91.2%, respondents who had socio-cultural support were 83.2%. The conclusion of this study is that there is no corelation between the level of knowledge and the use of contraception (p = 1,000), there is a corelation between information on health workers and the use of contraception (p = 0.002), there is a corelation between socio-culture and the use of contraception (p = 0.012) in the village of East Penfui Region. Tarus Community Health Center, Kupang Regency. The suggestion from this research is the need to communicate behavior change continuously to the public to increase awareness of using contraception. Keywords: contraception, knowledge, information, socio-culture